2015
DOI: 10.3390/ph8010062
|View full text |Cite
|
Sign up to set email alerts
|

Hitting the Bull’s-Eye in Metastatic Cancers—NSAIDs Elevate ROS in Mitochondria, Inducing Malignant Cell Death

Abstract: Tumor metastases that impede the function of vital organs are a major cause of cancer related mortality. Mitochondrial oxidative stress induced by hypoxia, low nutrient levels, or other stresses, such as genotoxic events, act as key drivers of the malignant changes in primary tumors to enhance their progression to metastasis. Emerging evidence now indicates that mitochondrial modifications and mutations resulting from oxidative stress, and leading to OxPhos stimulation and/or enhanced reactive oxygen species (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 279 publications
(368 reference statements)
0
44
0
Order By: Relevance
“…Hence, the pre-clinical findings are consistent with the ability of celecoxib to chemosensitize cancer cells rendering them more susceptible to other anticancer drugs. Drugs like celecoxib have proven to offer further advantages in that they have been shown to kill cancer cells independently of MDR [164,165] or p53 or DNA mismatch repair enzymes (reviewed in [152,166] ), because as we have shown, they kill by targeting mitochondrial metabolism [152][153][154]167] .…”
Section: Celecoxib In Combination With Chemotherapy Synergistically Imentioning
confidence: 97%
See 1 more Smart Citation
“…Hence, the pre-clinical findings are consistent with the ability of celecoxib to chemosensitize cancer cells rendering them more susceptible to other anticancer drugs. Drugs like celecoxib have proven to offer further advantages in that they have been shown to kill cancer cells independently of MDR [164,165] or p53 or DNA mismatch repair enzymes (reviewed in [152,166] ), because as we have shown, they kill by targeting mitochondrial metabolism [152][153][154]167] .…”
Section: Celecoxib In Combination With Chemotherapy Synergistically Imentioning
confidence: 97%
“…Previously, we reviewed the role of NSAIDs as "hitting the bulls-eye" in cancer cells by targeting mitochondrial function to trigger cell death via the intrinsic mitochondrial pathway of apoptosis [152] . Our more recent studies examined five different NSAIDs and showed that adding them to metastatic cancer cell lines in culture resulted in a progressive increase in ROS production from mitochondria to trigger ensuing cytotoxicity, by activating the intrinsic apoptotic signaling pathway.…”
Section: Nsaids Target Mitochondrial Ros Production To Trigger Apoptomentioning
confidence: 99%
“…However, this view has been challenged by numerous recent studies demonstrating that in several metastatic cancers, OxPhos is the predominant ATP cellular supplier in strong preference over glycolysis (Moreno-Sánchez et al, 2007;Ralph et al, 2010;Zu and Guppy, 2004). Thus, active OxPhos and mitochondrial remodeling and ROS production have been associated with invasiveness onset (Zhao et al, 2013), metastatic and malignant phenotype acquisition Ralph et al, 2015), cellular cycle activation and autophagy resistance (Salem et al, 2012), and other mechanisms implicated in drug resistance (Indran et al, 2011;Lu and Chao, 2012).…”
Section: Q5mentioning
confidence: 99%
“…Therefore, a more selective and specific targeting approach is needed that preferentially distinguishes cancer from normal cells. By changing the traditional approach of only looking for differences in the transcriptome or the proteome and instead searching for significant changes in function, such a target may be the reprogrammed redox metabolism found inside advanced stage cancer cells, particularly metastatic cells and cancer stem cells (CSCs; reviewed in Ralph et al and Skoda et al) (Table ).…”
Section: Introductionmentioning
confidence: 99%